Prefeitoperfeito.com: repositório de dados sobre engajamento digital eleitoral nas redes twitter e instagram, por meio do estudo de caso do segundo turno das eleições à prefeitura de São Luís, em 2020. - LACERDA, Bruno Ricardo Castro (2022)
This work proposes to develop a data repository (available at https://brlacerda.wixsite.com/prefeitoperfeito) on electoral digital engagement on Twitter and Instagram networks, through the case study of the second round of the executive election of São Luís Municipality, in 2020. In its construction, data was collected and analyzed on the digital campaign of candidates Eduardo Braide (then affiliated with “Podemos” party) and Duarte Junior (at that time, affiliated with “Republicanos” party), based on communicative patterns and trends, explored with Ltweet and Greenshot softwares, as well as Pandas and spaCy libraries. From the analysis, which made it possible to measure the variation of engagement in social networks and its impact on the electoral performance of candidates, it was evaluated that the number of publications on social networks is a secondary factor in the success of a digital campaign, underlying the quality of engagement generated by the developed communication strategy.